EFEKTIVITAS BREASTCARE TERHADAP PRODUKSI ASI IBU NIFAS DI WILAYAH KERJA PUSKESMAS PRUMNAS REJANG LEBONG BENGKULU - Puspita , Yenni (JURNAL KESEHATAN ALMUSLIM, 2019)
Breast care is an act to treat the breast especially during the puerperium (breastfeeding) to output breast milk. Based on the research that has been done was still a lot of childbed mothers who perform breast care is not good so that milk production is also a lot of not smooth. The purpose of this study was to determine the relationship of breast care with the smoothness of breast milk production in childbed mothers at Puskesmas Prumnas Rejang Lebong Working Area 2017 The design of this study was an analytical survey with a cohort approach. The population is all postpartum day 3-5 as many as 36 people, using random sampling technique, then the sample size used in this research as much as 36 people. The independent variable is breast care and the dependent variable is the smoothness of breast milk production The results showed that 10 respondents (50%) poor breast care and non-current milk production there were 14 respondents (70%). After analyzed, then obtained p = 0,003 with degree of meaning (α = 0,05). So the results obtained that p <α, mean H1 received means there is a relationship between breast care with the smoothness of breast milk production in childbed mothers at Puskesmas Prumnas Rejang Lebong Working Area 2017.